91. d d x x 3 , d e f i n i t i o n \frac{d}{dx}x^3, definition d x d x 3 , d e f i n i t i o n
d d x x 3 = lim h → 0 ( x + h ) 3 − x 3 h = 3 h x 2 + 3 h 2 x + h 3 h = lim h → 0 3 x 2 + 3 h x + h 2 = 3 x 2
\begin{aligned}
&\frac{d}{dx}x^3\\
&=\lim_{h\to0}\frac{(x+h)^3-x^3}{h}=\frac{3hx^2+3h^2x+h^3}{h}\\
&=\lim_{h\to0}3x^2+3hx+h^2=3x^2
\end{aligned}
d x d x 3 = h → 0 lim h ( x + h ) 3 − x 3 = h 3 h x 2 + 3 h 2 x + h 3 = h → 0 lim 3 x 2 + 3 h x + h 2 = 3 x 2
92. d d x 3 x + 1 , d e f . \frac{d}{dx} \sqrt{3x+1}, def. d x d 3 x + 1 , d e f .
d d x 3 x + 1 = lim h → 0 3 ( x + h ) + 1 − 3 x + 1 h = lim h → 0 ( 3 x + 3 h + 1 ) − ( 3 x + 1 ) h ( 3 x + 3 h + 1 + 3 x + 1 ) = lim h → 0 3 ( 3 x + 3 h + 1 + 3 x + 1 ) = 3 2 3 x + 1
\begin{aligned}
&\frac{d}{dx} \sqrt{3x+1}\\
&=\lim_{h\to0} \frac{\sqrt{3(x+h)+1}-\sqrt{3x+1}}{h}\\
&=\lim_{h\to0} \frac{(3x+3h+1)-(3x+1)}{h(\sqrt{3x+3h+1}+\sqrt{3x+1})}\\
&=\lim_{h\to0}\frac{3}{(\sqrt{3x+3h+1}+\sqrt{3x+1})}\\
&=\frac{3}{2\sqrt{3x+1}}
\end{aligned}
d x d 3 x + 1 = h → 0 lim h 3 ( x + h ) + 1 − 3 x + 1 = h → 0 lim h ( 3 x + 3 h + 1 + 3 x + 1 ) ( 3 x + 3 h + 1 ) − ( 3 x + 1 ) = h → 0 lim ( 3 x + 3 h + 1 + 3 x + 1 ) 3 = 2 3 x + 1 3
93. d d x 1 2 x + 5 , d e f . \frac{d}{dx} \frac{1}{2x+5}, def. d x d 2 x + 5 1 , d e f .
d d x 1 2 x + 5 = lim h → 0 1 2 ( x + h ) + 5 − 1 2 x + 5 h = − 2 h ( 2 x + 2 h + 5 ) ( 2 x + 5 ) h = lim h → 0 − 2 ( 2 x + 2 h + 5 ) ( 2 x + 5 ) = − 2 ( 2 x + 5 ) 2
\begin{aligned}
&\frac{d}{dx} \frac{1}{2x+5}\\
&=\lim_{h\to0} \frac{\frac{1}{2(x+h)+5}-\frac{1}{2x+5}}{h}=\frac{ \frac{-2h}{(2x+2h+5)(2x+5)}}{h}\\
&=\lim_{h\to0} -\frac{2}{(2x+2h+5)(2x+5)}\\
&=-\frac{2}{(2x+5)^2}
\end{aligned}
d x d 2 x + 5 1 = h → 0 lim h 2 ( x + h ) + 5 1 − 2 x + 5 1 = h ( 2 x + 2 h + 5 ) ( 2 x + 5 ) − 2 h = h → 0 lim − ( 2 x + 2 h + 5 ) ( 2 x + 5 ) 2 = − ( 2 x + 5 ) 2 2
94. d d x 1 x 2 , d e f . \frac{d}{dx}\frac{1}{x^2}, def. d x d x 2 1 , d e f .
d d x 1 x 2 = lim h → 0 1 ( x + h ) 2 − 1 x 2 h = − 2 x h − h 2 x 2 ( x + h ) 2 h = − 2 x − h x 2 ( x + h ) 2 = − 2 x x 4 = − 2 x 3
\begin{aligned}
&\frac{d}{dx}\frac{1}{x^2}\\
&=\lim_{h\to0} \frac{\frac{1}{(x+h)^2}-\frac{1}{x^2}}{h}= \frac{\frac{-2xh-h^2}{x^2(x+h)^2}}{h}=\frac{-2x-h}{x^2(x+h)^2}\\
&=\frac{-2x}{x^4}=-\frac{2}{x^3}
\end{aligned}
d x d x 2 1 = h → 0 lim h ( x + h ) 2 1 − x 2 1 = h x 2 ( x + h ) 2 − 2 x h − h 2 = x 2 ( x + h ) 2 − 2 x − h = x 4 − 2 x = − x 3 2
95. d d x s i n x , d e f . \frac{d}{dx}sinx, def. d x d s i n x , d e f .
d d x s i n x = lim h → 0 s i n ( x + h ) − s i n ( x ) h = lim h → 0 s i n ( x ) c o s ( h ) + c o s ( x ) s i n ( h ) − s i n ( x ) h = lim h → 0 s i n x ( c o s ( h ) − 1 ) h + c o s ( x ) s i n ( h ) h c o s ( h ) = 1 − h 2 2 ! + h 4 4 ! − . . . lim h → 0 c o s ( h ) − 1 h = h c + h 3 c + . . = O ( h ) = 0 s i n ( h ) = h − h 3 3 ! + . . . lim h → 0 s i n ( h ) h = 1 − O ( h 2 ) = 1 ∴ = s i n ( x ) 0 + c o s ( x ) 1 = c o s ( x )
\begin{aligned}
&\frac{d}{dx} sinx=\lim_{h\to0} \frac{sin(x+h)-sin(x)}{h}\\
&=\lim_{h\to0} \frac{ sin(x)cos(h)+cos(x)sin(h)-sin(x)}{h}\\
&=\lim_{h\to0} \frac{sinx(cos(h)-1)}{h}+cos(x)\frac{sin(h)}{h}\\
& cos(h)=1-\frac{h^2}{2!}+\frac{h^4}{4!}-...\\
& \lim_{h\to0} \frac{cos(h)-1}{h}=hc+h^3c+..=O(h)=0 \\
& sin(h)=h-\frac{h^3}{3!}+...\\
& \lim_{h\to0} \frac{sin(h)}{h}=1-O(h^2)=1\\
& \therefore =sin(x)0+cos(x)1=cos(x)
\end{aligned}
d x d s i n x = h → 0 lim h s i n ( x + h ) − s i n ( x ) = h → 0 lim h s i n ( x ) c o s ( h ) + c o s ( x ) s i n ( h ) − s i n ( x ) = h → 0 lim h s i n x ( c o s ( h ) − 1 ) + c o s ( x ) h s i n ( h ) c o s ( h ) = 1 − 2 ! h 2 + 4 ! h 4 − . . . h → 0 lim h c o s ( h ) − 1 = h c + h 3 c + . . = O ( h ) = 0 s i n ( h ) = h − 3 ! h 3 + . . . h → 0 lim h s i n ( h ) = 1 − O ( h 2 ) = 1 ∴ = s i n ( x ) 0 + c o s ( x ) 1 = c o s ( x )
96. d d x s e c x , d e f . \frac{d}{dx}secx, def. d x d s e c x , d e f .
d d x s e c ( x ) = lim h → 0 sec ( x + h ) − sec ( x ) h = lim h → 0 1 / cos ( x + h ) − 1 / cos ( x ) h = c o s ( x ) − c o s ( x + h ) c o s ( x + h ) c o s ( x ) h = c o s ( x ) − c o s ( x ) c o s ( h ) + s i n ( x ) s i n ( h ) ( c o s ( x ) c o s ( h ) − s i n ( x ) s i n ( h ) ) c o s ( x ) h = 1 − c o s ( h ) + t a n ( x ) s i n ( h ) h ( c o s ( x ) c o s ( h ) − s i n ( x ) s i n ( h ) ) = lim 1 c o s ( x ) c o s ( h ) − s i n ( x ) s i n ( h ) ( lim 1 − c o s ( h ) h + lim t a n ( x ) s i n ( h ) h ) = 1 c o s ( x ) ( 0 + t a n ( x ) ) = s e c ( x ) t a n ( x )
\begin{aligned}
&\frac{d}{dx}sec(x)=\lim_{h\to0}\frac{\sec(x+h)-\sec(x)}{h}\\
&=\lim_{h\to0}\frac{1/\cos(x+h)-1/\cos(x)}{h}=\frac{cos(x)-cos(x+h)}{cos(x+h)cos(x)h}\\
&=\frac{cos(x)-cos(x)cos(h)+sin(x)sin(h)}{(cos(x)cos(h)-sin(x)sin(h))cos(x)h}\\
&=\frac{1-cos(h)+tan(x)sin(h)}{h(cos(x)cos(h)-sin(x)sin(h))}\\
&=\lim \frac{1}{cos(x)cos(h)-sin(x)sin(h)} (\lim \frac{1-cos(h)}{h}+\lim \frac{tan(x)sin(h)}{h}) \\
&=\frac{1}{cos(x)}(0+tan(x))=sec(x)tan(x)
\end{aligned}
d x d s e c ( x ) = h → 0 lim h sec ( x + h ) − sec ( x ) = h → 0 lim h 1 / cos ( x + h ) − 1 / cos ( x ) = c o s ( x + h ) c o s ( x ) h c o s ( x ) − c o s ( x + h ) = ( c o s ( x ) c o s ( h ) − s i n ( x ) s i n ( h ) ) c o s ( x ) h c o s ( x ) − c o s ( x ) c o s ( h ) + s i n ( x ) s i n ( h ) = h ( c o s ( x ) c o s ( h ) − s i n ( x ) s i n ( h ) ) 1 − c o s ( h ) + t a n ( x ) s i n ( h ) = lim c o s ( x ) c o s ( h ) − s i n ( x ) s i n ( h ) 1 ( lim h 1 − c o s ( h ) + lim h t a n ( x ) s i n ( h ) ) = c o s ( x ) 1 ( 0 + t a n ( x ) ) = s e c ( x ) t a n ( x )
97. d d x a r c s i n x , d e f . \frac{d}{dx}arcsinx, def. d x d a r c s i n x , d e f .
d d x a r c s i n x = lim h → 0 a r c s i n ( x + h ) − a r c s i n ( x ) h
\begin{aligned}
&\frac{d}{dx}arcsinx=\lim_{h\to0} \frac{arcsin(x+h)-arcsin(x)}{h}\\
\end{aligned}
d x d a r c s i n x = h → 0 lim h a r c s i n ( x + h ) − a r c s i n ( x )
fail
d d x a r c s i n x = lim h → 0 a r c s i n ( x + h ) − a r c s i n ( x ) h s i n ( a − b ) = s i n a c o s b − s i n b c o s a arcsin s i n ( a − b ) = arcsin ( s i n a c o s b − s i n b c o s a ) a − b = arcsin ( s i n a c o s b − s i n b c o s a ) a = a r c s i n ( x + h ) , b = a r c s i n ( x ) a r c s i n ( x + h ) − a r c s i n ( x ) = a r c s i n ( s i n ( a r c s i n ( x + h ) ) c o s ( a r c s i n ( x ) ) − s i n ( a r c s i n ( x ) ) c o s ( a r c s i n ( x + h ) ) ) = a r c s i n ( ( x + h ) c o s ( a r c s i n ( x ) ) − x c o s ( a r c s i n ( x + h ) ) ) ( c o s ( x ) = 1 − s i n 2 ( x ) ) We know, lim x → 0 s i n x x = 1 , lim x → 0 s i n ( x ) = lim x → 0 x S o , lim x → 0 s i n − 1 ( x ) = lim x → 0 x = a r c s i n ( ( x + h ) 1 − x 2 − x 1 − ( x + h ) 2 ) d d x a r c s i n x = lim h → 0 a r c s i n ( x + h ) − a r c s i n ( x ) h = lim h → 0 a r c s i n ( ( x + h ) 1 − x 2 − x 1 − ( x + h ) 2 ) h = lim h → 0 ( x + h ) 1 − x 2 − x 1 − ( x + h ) 2 h = lim h → 0 ( x + h ) 2 ( 1 − x 2 ) − x 2 ( 1 − ( x + h ) 2 ) h ( ( x + h ) 1 − x 2 + x 1 − ( x + h ) 2 ) N u m e r a t o r = ( x + h ) 2 − x 2 ( x + h ) 2 − x 2 + x 2 ( x + h ) 2 N u m e r a t o r = ( x + h ) 2 − x 2 = 2 x h + h 2 = lim h → 0 2 x + h ( x + h ) 1 − x 2 + x 1 − ( x + h ) 2 = 2 x x 1 − x 2 + x 1 − x 2 = 2 x 2 x 1 − x 2 = 1 1 − x 2
\begin{aligned}
&\frac{d}{dx}arcsinx=\lim_{h\to0} \frac{arcsin(x+h)-arcsin(x)}{h}\\
& sin(a-b) = sinacosb-sinbcosa\\
& \arcsin {sin(a-b)} = \arcsin {(sinacosb-sinbcosa)}\\
& a-b = \arcsin {(sinacosb-sinbcosa)}\\
& a=arcsin(x+h), b=arcsin(x)\\
&arcsin(x+h)-arcsin(x) = arcsin(sin(arcsin(x+h))cos(arcsin(x))-sin(arcsin(x))cos(arcsin(x+h)))\\
&=arcsin((x+h)cos(arcsin(x))-xcos(arcsin(x+h)))\\
& (cos(x) = \sqrt {1-sin^2(x)}) \\
& \text{We know,} \lim_{x\to0} \frac{sin x}{x}=1, \lim _{x\to0} sin(x) = \lim_{x\to0} x\\
&So, \lim_{x\to0} sin^{-1}(x)=\lim_{x\to0}x
&=arcsin( (x+h) \sqrt{1-x^2}-x\sqrt{1-(x+h)^2} )\\
&\frac{d}{dx}arcsinx=\lim_{h\to0} \frac{arcsin(x+h)-arcsin(x)}{h}\\
&=\lim_{h\to0} \frac{arcsin( (x+h) \sqrt{1-x^2}-x\sqrt{1-(x+h)^2} )}{h}\\
&=\lim_{h\to0} \frac{ (x+h) \sqrt{1-x^2}-x\sqrt{1-(x+h)^2} }{h} \\
&=\lim_{h\to0} \frac{ (x+h)^2(1-x^2)-x^2(1-(x+h)^2)} {h ((x+h) \sqrt{1-x^2}+x\sqrt{1-(x+h)^2} )} \\
&Numerator=(x+h)^2-x^2(x+h)^2-x^2+x^2(x+h)^2\\
&Numerator=(x+h)^2-x^2=2xh+h^2\\
&=\lim_{h\to0} \frac{ 2x+h} {(x+h) \sqrt{1-x^2}+x\sqrt{1-(x+h)^2} } \\
&=\frac{2x}{x\sqrt{1-x^2}+x\sqrt{1-x^2}}=\frac{2x}{2x\sqrt{1-x^2}}\\
&=\frac{1}{\sqrt{1-x^2}}
\end{aligned}
d x d a r c s i n x = h → 0 lim h a r c s i n ( x + h ) − a r c s i n ( x ) s i n ( a − b ) = s i n a c o s b − s i n b c o s a arcsin s i n ( a − b ) = arcsin ( s i n a c o s b − s i n b c o s a ) a − b = arcsin ( s i n a c o s b − s i n b c o s a ) a = a r c s i n ( x + h ) , b = a r c s i n ( x ) a r c s i n ( x + h ) − a r c s i n ( x ) = a r c s i n ( s i n ( a r c s i n ( x + h ) ) c o s ( a r c s i n ( x ) ) − s i n ( a r c s i n ( x ) ) c o s ( a r c s i n ( x + h ) ) ) = a r c s i n ( ( x + h ) c o s ( a r c s i n ( x ) ) − x c o s ( a r c s i n ( x + h ) ) ) ( c o s ( x ) = 1 − s i n 2 ( x ) ) We know, x → 0 lim x s i n x = 1 , x → 0 lim s i n ( x ) = x → 0 lim x S o , x → 0 lim s i n − 1 ( x ) = x → 0 lim x d x d a r c s i n x = h → 0 lim h a r c s i n ( x + h ) − a r c s i n ( x ) = h → 0 lim h a r c s i n ( ( x + h ) 1 − x 2 − x 1 − ( x + h ) 2 ) = h → 0 lim h ( x + h ) 1 − x 2 − x 1 − ( x + h ) 2 = h → 0 lim h ( ( x + h ) 1 − x 2 + x 1 − ( x + h ) 2 ) ( x + h ) 2 ( 1 − x 2 ) − x 2 ( 1 − ( x + h ) 2 ) N u m e r a t o r = ( x + h ) 2 − x 2 ( x + h ) 2 − x 2 + x 2 ( x + h ) 2 N u m e r a t o r = ( x + h ) 2 − x 2 = 2 x h + h 2 = h → 0 lim ( x + h ) 1 − x 2 + x 1 − ( x + h ) 2 2 x + h = x 1 − x 2 + x 1 − x 2 2 x = 2 x 1 − x 2 2 x = 1 − x 2 1 = a r c s i n ( ( x + h ) 1 − x 2 − x 1 − ( x + h ) 2 )
98. d d x a r c t a n x , d e f . \frac{d}{dx}arctanx, def. d x d a r c t a n x , d e f .
Try like upper case, lim tan(x)/x = 1, atan(x)/x=1
d d x a r c t a n ( x ) = lim h → 0 a r c t a n ( x + h ) − a r c t a n ( x ) h t a n ( a − b ) = t a n ( a ) − t a n ( b ) 1 + t a n ( a ) t a n ( b ) a − b = a r c t a n ( t a n ( a ) − t a n ( b ) 1 + t a n ( a ) t a n ( b ) ) N u m e r a t o r = a r c t a n ( x + h ) − a r c t a n ( x ) N = a r c t a n ( t a n ( a r c t a n ( x + h ) ) − t a n ( a r c t a n ( x ) ) 1 + t a n ( a r c t a n ( x + h ) ) t a n ( a r c t a n ( x ) ) ) = a r c t a n ( x + h − x 1 + ( x + h ) x ) = a r t a n ( h 1 + x 2 + h x ) S o , d d x a r c t a n ( x ) = lim h → 0 a r c t a n ( x + h ) − a r c t a n ( x ) h = lim h → 0 a r t a n ( h 1 + x 2 + h x ) h = lim h → 0 1 1 + x 2 + h x = 1 1 + x 2
\begin{aligned}
&\frac{d}{dx}arctan(x)=\lim_{h\to0} \frac{arctan(x+h)-arctan(x)}{h}\\
& tan(a-b)=\frac{tan(a)-tan(b)}{1+tan(a)tan(b)}\\
& a-b = arctan(\frac{tan(a)-tan(b)}{1+tan(a)tan(b)})\\
&Numerator=arctan(x+h)-arctan(x)\\
&N=arctan( \frac{tan(arctan(x+h))-tan(arctan(x))}{1+tan(arctan(x+h))tan(arctan(x))} )\\
&=arctan( \frac{x+h-x}{1+(x+h)x} )=artan(\frac{h}{1+x^2+hx})\\
&So, \\
&\frac{d}{dx}arctan(x)=\lim_{h\to0} \frac{arctan(x+h)-arctan(x)}{h}\\
&=\lim_{h\to0} \frac{artan(\frac{h}{1+x^2+hx})}{h}\\
&=\lim_{h\to0} \frac{1}{1+x^2+hx}=\frac{1}{1+x^2}\\
\end{aligned}
d x d a r c t a n ( x ) = h → 0 lim h a r c t a n ( x + h ) − a r c t a n ( x ) t a n ( a − b ) = 1 + t a n ( a ) t a n ( b ) t a n ( a ) − t a n ( b ) a − b = a r c t a n ( 1 + t a n ( a ) t a n ( b ) t a n ( a ) − t a n ( b ) ) N u m e r a t o r = a r c t a n ( x + h ) − a r c t a n ( x ) N = a r c t a n ( 1 + t a n ( a r c t a n ( x + h ) ) t a n ( a r c t a n ( x ) ) t a n ( a r c t a n ( x + h ) ) − t a n ( a r c t a n ( x ) ) ) = a r c t a n ( 1 + ( x + h ) x x + h − x ) = a r t a n ( 1 + x 2 + h x h ) S o , d x d a r c t a n ( x ) = h → 0 lim h a r c t a n ( x + h ) − a r c t a n ( x ) = h → 0 lim h a r t a n ( 1 + x 2 + h x h ) = h → 0 lim 1 + x 2 + h x 1 = 1 + x 2 1
99. d d x f ( x ) g ( x ) , d e f . \frac{d}{dx}f(x)g(x), def. d x d f ( x ) g ( x ) , d e f .
d d x f ( x ) g ( x ) = lim h → 0 f ( x + h ) g ( x + h ) − f ( x ) g ( x ) h = lim h → 0 f ( x + h ) g ( x + h ) − f ( x ) g ( x ) − g ( x + h ) f ( x ) + g ( x + h ) f ( x ) h = lim h → 0 g ( x + h ) ( f ( x + h ) − f ( x ) ) + f ( x ) ( g ( x + h ) − g ( x ) ) h = lim h → 0 g ( x + h ) f ( x + h ) − f ( x ) h + f ( x ) g ( x + h ) − g ( x ) h = g ( x ) f ′ ( x ) + f ( x ) g ′ ( x ) = f ′ ( x ) g ( x ) + f ( x ) g ′ ( x )
\begin{aligned}
&\frac{d}{dx}f(x)g(x)=\lim_{h\to0}\frac{f(x+h)g(x+h)-f(x)g(x)}{h}\\
&=\lim_{h\to0}\frac{f(x+h)g(x+h)-f(x)g(x)-g(x+h)f(x)+g(x+h)f(x)}{h}\\
&=\lim_{h\to0} \frac{g(x+h)(f(x+h)-f(x))+f(x)(g(x+h)-g(x))}{h}\\
&=\lim_{h\to0} g(x+h)\frac{f(x+h)-f(x)}{h}+f(x)\frac{g(x+h)-g(x)}{h}\\
&=g(x)f'(x)+f(x)g'(x)=f'(x)g(x)+f(x)g'(x)
\end{aligned}
d x d f ( x ) g ( x ) = h → 0 lim h f ( x + h ) g ( x + h ) − f ( x ) g ( x ) = h → 0 lim h f ( x + h ) g ( x + h ) − f ( x ) g ( x ) − g ( x + h ) f ( x ) + g ( x + h ) f ( x ) = h → 0 lim h g ( x + h ) ( f ( x + h ) − f ( x ) ) + f ( x ) ( g ( x + h ) − g ( x ) ) = h → 0 lim g ( x + h ) h f ( x + h ) − f ( x ) + f ( x ) h g ( x + h ) − g ( x ) = g ( x ) f ′ ( x ) + f ( x ) g ′ ( x ) = f ′ ( x ) g ( x ) + f ( x ) g ′ ( x )
100. d d x f ( x ) g ( x ) , d e f . \frac{d}{dx} \frac{f(x)}{g(x)}, def. d x d g ( x ) f ( x ) , d e f .
d d x f ( x ) g ( x ) = lim h → 0 f ( x + h ) g ( x + h ) − f ( x ) g ( x ) h = f ( x + h ) g ( x ) − f ( x ) g ( x + h ) g ( x ) g ( x + h ) h = f ( x + h ) g ( x ) − f ( x ) g ( x + h ) − g ( x ) f ( x ) + g ( x ) f ( x ) h g ( x ) g ( x + h ) = g ( x ) ( f ( x + h ) − f ( x ) ) − f ( x ) ( g ( x + h ) − g ( x ) ) h g ( x ) g ( x + h ) = g ( x ) f ′ ( x ) − f ( x ) g ′ ( x ) g ( x ) 2
\begin{aligned}
&\frac{d}{dx} \frac{f(x)}{g(x)}=\lim_{h\to0}\frac{ \frac{f(x+h)}{g(x+h)} - \frac{f(x)}{g(x)}}{h} =\frac{ \frac{f(x+h)g(x)-f(x)g(x+h)}{g(x)g(x+h)} }{h}\\
&=\frac{ f(x+h)g(x)-f(x)g(x+h)-g(x)f(x)+g(x)f(x)}{hg(x)g(x+h)}\\
&=\frac{g(x)(f(x+h)-f(x))-f(x)(g(x+h)-g(x))}{hg(x)g(x+h)}\\
&=\frac{g(x)f'(x)-f(x)g'(x)}{g(x)^2}
\end{aligned}
d x d g ( x ) f ( x ) = h → 0 lim h g ( x + h ) f ( x + h ) − g ( x ) f ( x ) = h g ( x ) g ( x + h ) f ( x + h ) g ( x ) − f ( x ) g ( x + h ) = h g ( x ) g ( x + h ) f ( x + h ) g ( x ) − f ( x ) g ( x + h ) − g ( x ) f ( x ) + g ( x ) f ( x ) = h g ( x ) g ( x + h ) g ( x ) ( f ( x + h ) − f ( x ) ) − f ( x ) ( g ( x + h ) − g ( x ) ) = g ( x ) 2 g ( x ) f ′ ( x ) − f ( x ) g ′ ( x )
101. d d x x x x \frac{d}{dx} x^{{x}^{x}} d x d x x x
First,d d x x x y = x x , l n y = x l n x , ( 1 / y ) y ′ = l n x + x ( 1 / x ) y ′ = y l n x + y = x x l n x + x x
\frac{d}{dx}x^x\\
y=x^x, lny=xlnx, (1/y)y'=lnx+x(1/x)\\
y'=ylnx+y=x^xlnx+x^x
d x d x x y = x x , l n y = x l n x , ( 1 / y ) y ′ = l n x + x ( 1 / x ) y ′ = y l n x + y = x x l n x + x x
Second,
d d x x x x y = x x x l n y = x x l n ( x ) 1 y y ′ = ( x x l n x + x x ) l n ( x ) + x x 1 x = x x ( ( l n x ) 2 + l n ( x ) + 1 x ) y ′ = x x x x x ( ( l n x ) 2 + l n ( x ) + 1 x )
\begin{aligned}
&\frac{d}{dx} x^{x^{x}}\\
&y=x^{x^{x}} \\
&ln y = x^x ln(x) \\
&\frac{1}{y} y' = (x^xlnx+x^x)ln(x)+x^x\frac{1}{x}\\
&=x^x((lnx)^2+ln(x)+\frac{1}{x})\\
&y'=x^{x^x}x^x((lnx)^2+ln(x)+\frac{1}{x})\\
\end{aligned}
d x d x x x y = x x x l n y = x x l n ( x ) y 1 y ′ = ( x x l n x + x x ) l n ( x ) + x x x 1 = x x ( ( l n x ) 2 + l n ( x ) + x 1 ) y ′ = x x x x x ( ( l n x ) 2 + l n ( x ) + x 1 )
The END
Author: crazyj7@gmail.com